An Electronic Grading and Reporting System - Keneth Muhwezi (Uganda Christian University, 2025)
The proposed project is an Electronic Grading and Reporting System for Bishop Ruhindi High School located in Rukungiri District, Uganda. With the implementation of the new curriculum by the National Curriculum Development Centre (NCDC), schools are facing challenges in adopting a grading management system that aligns with the new curriculum. This study aimed to design and develop a system to streamline the grading and reporting process for Bishop Ruhindi High School, covering four classrooms (S1, S2, S3 and S4) with a provision to extend further to Advanced level. The project made use of a combination involving HTML, CSS, PHP, MySQL, JavaScript, and JQuery. The system was developed utilizing Bootstrap. It was specifically designed to be accessible by the system administrator and instructors, with full rights to the system by the admin, including registering Students and teachers, entering marks, monitoring performance, and printing reports. The final examination of project methodology indicates that the Electronic Grading and Reporting System could assist with automating the grading and reporting process, enhance consistency and effectiveness, and establish a process to assess and refine the learning process at Bishop Ruhindi High School will experience an installation with state-of-the-art and user-friendly functionality. A sound way to manage the process of assessing and documenting. In short, the Electronic Grading and Reporting System is a huge leap towards improving the Uganda education system, and by extension Bishop Ruhindi High School. The system is aimed at addressing challenges faced by learning facilities when running the new curriculum, and offers a framework for assessing and enhancing the learning process.
Undergraduate Research